PENDEKATAN PEMBELAJARAN PENEMUAN (DISCOVERY LEARNING) SEBAGAI UPAYA MENINGKATKAN KETERAMPILAN DISKUSI SISWA KELAS XI MIA 4 SMA NEGERI 1 KERAMBITAN KABUPATEN TABANAN - Widiasa, I Made (Widyadari : Jurnal Pendidikan, 2019)
In the reality and teaching experience in SMA Negeri 1 Kerambitan, Tabanan regency, the use of discussion method can't run like as we hope. That is caused by both of the teacher who can understand or comprehend their role in the discussion. The discussion method is one of the method which is qualified by the 2013 curriculum. That is why important to improve the discission method on teaching and learning activity and to increase the student and the teachers skill in discussing, one of the effort is whit Discovery Learning. Discovery learning approach is mentioned as Discovery Guided, that is Discovery learning where the students in choosing the matter of the lesson, the kinds of data which is collected and the discussion are guided by the teachers. The aplication of this approach uses student work sheet (LKS) type B and C. The role of the teachers in the discussion are as moderator, consultant, motivator, encourager, and evaluator. All of these have purpose to increase the skill in discussion which cover communication skill, skill of presenting opinion, and can appreciate the other person's idea, has skill to make decision. Now the phase of the Actions learning which the teacher (researcher) does to reach the objective is to give the stimulation to motivate the students in studying, identifying the problems which will be solved by the students then collect the data, and has the discussion to reach the truth of the data which they got and is ended by making agreement to find one meaning in the conclusion. The data analyze which is used in this research is qualitative descriptive approach, the result of this research shows that discovery learning approach can increase the skill in discussion on both of students and teachers. This can be seen that there is incresing of the discussion skill of the students up to 75% and the teacher reach more than 85%. By the classroom Actions research the teachers can reach the teaching purpose as they expect.